Comparison Of The Amino Acid Sequence Of L-Mandelate Dehydrogenase From Rhodotorula Graminis With Other L-2-Hydroxyacid Dehydrogenase Enzyme And Its Primary Structure Prediction - Md. Illias, Rosli; Reid, Graeme A.; A. Wahab, Nadzarah (Penerbit UTM Press, 2001)
A comparison of the primary structure for L-mandelate dehydrogenase (L-MDH) from Rhodotorula graminis with other proteins from the protein databank suggests that there is similarity between this protein and L-2-hydroxyacid dehydrogenase enzymes. R. graminis LMDH exhibits 26–42% identity to L-lactate dehydrogenase from Saccharomyces cerevisiae, L-lactate dehydrogenase from Hansenula anomala, glycolate oxidase from spinach, L-lactate dehydrogenase from Escherichia coli, L-mandelate dehydrogenase from Pseudomonas putida and lactate-2-monooxygenase from Mycobacterium smegmatis. Structurally conserved amino acids are predicted from LMDH sequences corresponding to important regions of the cytochrome and FMN-binding domain defined from the known three-dimensional structure of the L-lactate dehydrogenase from Saccharomyces cerevisiae.